2018
DOI: 10.1146/annurev-bioeng-062117-121156
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the Mucus Barrier

Abstract: Mucus selectively controls the transport of molecules, particulate matter, and microorganisms to the underlying epithelial layer. It may be desirable to weaken the mucus barrier to enable effective delivery of drug carriers. Alternatively, the mucus barrier can be strengthened to prevent epithelial interaction with pathogenic microbes or other exogenous materials. The dynamic mucus layer can undergo changes in structure (e.g., pore size) and/or composition (e.g., protein concentrations, mucin glycosylation) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
83
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(85 citation statements)
references
References 147 publications
1
83
0
1
Order By: Relevance
“…Despite the common opinion that mucoadhesion of particles, such as drug nanocarriers, can improve the GI absorption of orally administered pharmaceuticals by increasing their retention in mucus 42,43 , more and more studies have shown that altering surface chemistry of particles in a way that allows them to penetrated mucus and avoid mucoadhesion can enhance drug delivery in the GI tract 19,[44][45][46] . Mucoadhesive particles are vulnerable to clearance, as the mucus is ultimately cleared through muscular contractions such as peristalsis, resulting in particles moving distally with the intestinal contents 47 . Positively charged particles are especially prone to adhering to the GI mucus 46,48 , which is largely due to the electrostatic attraction to negatively charged mucus.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the common opinion that mucoadhesion of particles, such as drug nanocarriers, can improve the GI absorption of orally administered pharmaceuticals by increasing their retention in mucus 42,43 , more and more studies have shown that altering surface chemistry of particles in a way that allows them to penetrated mucus and avoid mucoadhesion can enhance drug delivery in the GI tract 19,[44][45][46] . Mucoadhesive particles are vulnerable to clearance, as the mucus is ultimately cleared through muscular contractions such as peristalsis, resulting in particles moving distally with the intestinal contents 47 . Positively charged particles are especially prone to adhering to the GI mucus 46,48 , which is largely due to the electrostatic attraction to negatively charged mucus.…”
Section: Resultsmentioning
confidence: 99%
“…The specific molecular properties that promote the adhesion of a molecule to a mucus barrier, and specifically to the mucin polymers, remain poorly understood (Carlson et al 2018, Newby et al 2018, Witten et al 2018. For example, more positively charged molecules bind more strongly to net negatively charged mucin (Witten et al 2018).…”
Section: Influence Of Mucin Biochemistry On the Permeability Of Mucusmentioning
confidence: 99%
“…However, Li et al (2013) reported that with alternating blocks of positive and negative charge, small peptides interact more strongly with mucins than do peptides of the same overall charge but with singly alternating charges, highlighting the importance of both charge magnitude and spatial arrangement. Furthermore, the presence of hydrophobic moieties on a molecule increases its degree of binding to mucus, but it is believed that spatial arrangements of proximal charge and other chemical parameters on the molecule in question are also important (Carlson et al 2018, Witten et al 2018). An improved understanding of the mechanisms that determine adhesiveness to the mucus barrier will therefore be critical for the design of particles with specific transport rates through mucus, including in the context of optimizing drug delivery.…”
Section: Influence Of Mucin Biochemistry On the Permeability Of Mucusmentioning
confidence: 99%
“…It is a useful method to ameliorate the chemical properties and to prepare new materials with potential uses in different applications. Zwitterions are compounds which contain positively and negatively charged groups resulting in an overall neutral charge [ 35 ]. As materials, they are able to reduce non-specific protein adsorption as well as bacterial adhesion, and provide an increased bioavailability [ 36 ].…”
Section: Introductionmentioning
confidence: 99%